Financial audit of antitachycardia pacing for the control of recurrent supraventricular tachycardia. Issue 3 (March 1993) - Griffith, M J; Bexton, R S; McComb, J M
Abstract : OBJECTIVE--To assess the financial implications of antitachycardia pacing in patients with frequent supraventricular tachycardia. PATIENTS--Intertach pacemakers were implanted in 25 patients (mean age 47 years, five men): 22 had atrioventricular nodal reentry tachycardia. The patients had failed a mean of 4.9 (range zero to eight) drugs and had been admitted to hospital 3.7 (zero to 31) times over a symptomatic period of 13.9 years (two months to 54 years). RESULTS--The mean admission time for implantation was 2.8 (two to seven) days. One patient with Wolff-Parkinson-White syndrome subsequently underwent surgery. Infection occurred in two patients, and pain over the pacemaker required its resiting in two. Two patients have had one admission each for tachycardia. Six patients remain on anti-arrhythmic drugs. Costs were calculated including value added tax, capital charges, and allocated overheads. The cost a year before pacing was 1174 pounds including drug costs, clinic visits, and hospital admissions. The mean cost of pacemaker implantation was 3364.22 pounds, including the pacemaker and lead, admission and procedure, readmissions and first pacing check. Subsequent annual follow up cost was 73.72 pounds including annual clinic visits and drug costs. The cost of pacing is 4241 pounds whereas medical management costs 7044 pounds assuming pacemaker life of six years: with a 10 year life the cost is 4537 pounds compared with 11, 740 pounds: with a 12 year life the cost is 4685 pounds compared with 14, 088 pounds. CONCLUSION--The excess cost of implantation of an antitachycardia pacemaker is minimal in patients with frequent supraventricular tachycardia despite drug treatment and is justified by excellent control of symptoms and reduction of drug use and hospital admissions.